Probability reliability of technical protection of information depending on background - Журиленко, Борис Евгеньевич; Николаева, Надежда Константиновна (Ukrainian Information Security Research Journal, 2018)
This paper presents a theoretical study of the proposed new direction in the design, analysis of the state and timely modernization of the operating technical information protection (TZI) depending on the hacking process in the di-rection of hacking. Based on the risks of protection of TZI, the function inherent in this technical protection is ob-tained, depending on the parameters of the direction of the hacking process and determining the probabilistic reliability of technical protection in the direction of hacking. It is shown that this function meets the physical requirements of the hacking process. An expression is obtained from the direction function of the hacking process, which allows one or another unknown time or attempt parameter to be determined from the parameters of the attempt or the time of the hacking. For example, by a known hacking attempt, it is possible to estimate the possible time when a TZI hacking will occur, or, conversely, to determine an attempt by a known time. In this paper, the distribution of the maximums of the probability of breaking into technical protec-tion is obtained for directions of breaking depending on the parameters of the attempt, the time of this attempt and the protection effectiveness ratio. It should be noted that the actual process of hacking is a random variable, both in attempts and in the time of hacking, so the direction of hacking is not displayed as a straight line. In real conditions, the direction of hacking can be determined according to the methodology, as proposed in the works of B. Zhurilenko, in a straight line. In this case, the direction of the line is defined as the rms or mean value of the results of the attempts and its hacking time. As a result of the studies carried out according to the obtained theoretical expressions, the distribution surface of the maxima of probabilis-tic cracking of the CRT and the probability in the direction of the cracking process line, depending on its two parameters - the number of the attempt and its cracking time, are constructed. The resulting expressions will be of great importance in the design, analysis of the working state of the working TZI and modernization of protection to save the invested financial costs in protection.